Shorter average look durations to dynamic social stimuli are associated with higher levels of autism symptoms in young autistic children. (August 2022) - Major, Samantha; Isaev, Dmitry; Grapel, Jordan; Calnan, Todd; Tenenbaum, Elena; Carpenter, Kimberly; Franz, Lauren; Howard, Jill; Vermeer, Saritha; Sapiro, Guillermo; Murias, Michael; Dawson, Geraldine
Prior eye-tracking studies involving autistic individuals have focused on total looking time or proportion of looking time to key regions of interest. These studies have not examined another important feature, the ability to sustain attention to stimuli. In particular, the ability to sustain attention to a dynamic social stimulus might reflect more advanced self-regulatory skills that may enhance engagement with and comprehension of social information. In a sample of 155 autistic children (2–8 years of age), we examined children's average look duration while they viewed a complex, dynamic stimulus containing both social and nonsocial elements. After accounting for children's age and intelligence quotient, we found that shorter average look duration was associated with increased autism spectrum disorder severity across multiple clinical measures. To calculate average look duration, we divided the length of total looking time in seconds by the total number of uninterrupted looks to the video media. Thus, the ability to sustain attention while viewing complex dynamic information could be important for comprehending dynamic social information. Lay Abstract: Many studies of autism look at the differences in how autistic research participants look at certain types of images. These studies often focus on where research participants are looking within the image, but that does not tell us everything about how much they are paying attention. It could be useful to know more about how well autistic research participants can focus on an image with people in it, because those who can look at images of people for longer duration without stopping may be able to easily learn other skills that help them to interact with people. We measured how long autistic research participants watched the video without breaking their attention. The video sometimes had a person speaking, and at other times had toys moving and making sounds. We measured the typical amount of time autistic research participants could look at the video before they looked away. We found that research participants with more severe autism tended to look at the video for shorter amounts of time. The ability to focus without stopping may be related to social skills in autistic people.